Dastgāhʻhā-yi mūsīqī-i sunnatī-i Īrān - Ma'aroufi, Moussa (Intishārāt-i Instītū-yi Taḥqīqāt-i Mūsīqīʻshināsī Īrān, Farhangistān-i Adab va Hunar, 1977)
Conventional classification of the traditional music of Iran; includes musical notations.